University Professors' Epistemic Authority Assessment in Actual and Time-Remote Interaction - Blumberga, Solveiga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The epistemological aspect of knowledge is described as a subject of psychology and pedagogy studies, students’ views about learning or acquisition of knowledge and learning skills, role of experience in which knowledge is construed. Epistemic authority is related to the social context, interaction within this context in which transmission and exchange of knowledge take place and which is studied in the concept of social epistemology. Studies into epistemological views of students reveal the specifics of academic areas: students may have views about knowledge in general, this influences their behaviour, but they may differ in academic areas. Epistemic authority was explained as an essential factor in the process of acquisition of knowledge in schools and universities. An empirical study consisting of two stages was conducted to investigate student-perceived epistemic authority of university professors. Research target is to find out the level of assessment of perceived epistemic authority of university professors in the student and graduate samples and in study area groups. Author use epistemic authority research methodology, which include survey - Epistemic Authority Scale. A comparison of the results on the level of the sample shows that the results of study one  and two are similar to the results obtained in the original study, and this, in general, suggests similar tendencies in assessment of professors’ epistemic authority regardless of cultural environment and the time distance when the measurements were made.